The distribution and spectrum of thalassemia variants in GUIYANG region, southern China - Xuanyin Zhao; Zhiyu You; Yunyan Deng; Yi Zhou; Dongyang Deng; Jian Quan; Fang Chen; Zhimei Yan; Ya Qi; Leilei Chen; Fang Xiang; Weixian Zheng; et al. (Orphanet Journal of Rare Diseases, 2025)
Abstract Thalassemia is one of southern China’s most common inherited disorders. This retrospective study analyzed the results of thalassemia gene testing conducted on 20,478 individuals from January 1, 2019, to April 31, 2024 in the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine. The cohort consisted of 19,733 females and 745 males, with 1401 individuals testing positive for thalassemia. Among the positive cases, 942 had α thalassemia, 431 had β thalassemia, and 25 had variants in both α and β thalassemia genes. Interestingly, a subgroup of individuals with thalassemia variants not previously documented in medical literature was identified. The study highlighted the prevalence of thalassemia among different ethnic groups, with individuals of Han ethnicity being the most affected. Geographical analysis revealed a concentration of cases in Guizhou Province, particularly in Guiyang city, Bijie, and Qiannan Prefecture. These findings provide valuable insights into the epidemiology of thalassemia in the region and the distribution of affected individuals.